Application of concentrated deep sea water inhibits the development of atopic dermatitis-like skin lesions in NC/Nga mice - Bak Jong-Phil; Kim Yong-Min; Son Jeonghyun; Kim Chang-Ju; Kim Ee-Hwa (BMC, 2012)
Abstract Background Mineral water from deep-sea bedrock, formed over thousands of years, is rich in minerals such as Ca, Mg, Na, K, Fe and others. Our present study was to investigate the preventive effects of natural deep-sea water on developing atopic dermatitis (AD). Methods We elicited AD by application of DNCB (2,4-dinitro-chlorobezene) in Nc/Nga mouse dorsal skin. Deep Sea water (DSW) was filtered and concentrated by a nanofiltration process and reverse osmosis. We applied concentrated DSW (CDSW) to lesions five times per week for six weeks, followed by evaluation. 1% pimecrolimus ointment was used as positive control. The severity of skin lesions was assessed macroscopically and histologically. Levels of inflammatory mediators and cytokines in the serum were detected by Enzyme-linked immunosorbent assay (ELISA) and the levels of CD4+ and CD8+ spleen lymphocytes were determined by flow cytometry analysis. Results DNCB-treated mice showed atopic dermatitis-like skin lesions. Treatment of mice with CDSW reduced the severity of symptoms in the skin lesions, including edema, erythema, dryness, itching, and transepidermal water loss (TEWL). Histological analyses demonstrated that epidermal thickness and infiltration of inflammatory cells were decreased after CDSW treatment. Given these interesting observations, we further evaluated the effect of CDSW on immune responses in this AD model. Treatment AD mice with CDSW inhibited up-regulation of IgE, histamine, and pro-inflammatory cytokines in the serum. Also, the CD4+/CD8+ ratio in spleen lymphocyte was down-regulated after treatment with CDSW. Finally, cytokines, especially IL-4 and IL-10 which are important for Th2 cell development, were reduced. Conclusions Our data suggests that topical application of CDSW could be useful in preventing the development of atopic dermatitis.